2021
DOI: 10.5009/gnl20036
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitor-Related Gastric Mucosal Changes

Abstract: Proton pump inhibitors (PPIs) are used worldwide to treat of acid-related disorders such as peptic ulcer and gastroesophageal reflux disease and to prevent gastroduodenal injuries due to nonsteroidal anti-inflammatory drugs. PPIs are the most potent inhibitors of gastric acid secretion currently available, and they are one of the most commonly prescribed classes of drugs because of their high efficacy and low toxicity. However, long-term PPI use causes histopathological changes such as parietal cell protrusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 34 publications
1
54
1
1
Order By: Relevance
“…Suppression of gastric acid secretion by long-term PPI administration has been reported to increase serum gastrin levels [ 12 ], causing histopathological changes, such as parietal cell protrusions and dilated oxyntic glands [ 13 ]. In addition, it is speculated that hypergastrinemia causes HPs due to hyperplasia of the gastric foveolar epithelium [ 14 ]. In the present case, after 14 years of PPI therapy, there was not only evidence of hypergastrinemia (gastrin, 1,060 pg/mL) but a histological examination also revealed parietal cell protrusions and dilated oxyntic glands, which appeared to support the hypothesis that this case constituted one of PPI-associated HPs.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Suppression of gastric acid secretion by long-term PPI administration has been reported to increase serum gastrin levels [ 12 ], causing histopathological changes, such as parietal cell protrusions and dilated oxyntic glands [ 13 ]. In addition, it is speculated that hypergastrinemia causes HPs due to hyperplasia of the gastric foveolar epithelium [ 14 ]. In the present case, after 14 years of PPI therapy, there was not only evidence of hypergastrinemia (gastrin, 1,060 pg/mL) but a histological examination also revealed parietal cell protrusions and dilated oxyntic glands, which appeared to support the hypothesis that this case constituted one of PPI-associated HPs.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…3 In addition, PPIs have several adverse effects in the stomach, such as oxyntic cell and enterochromaffin-like cell hyperplasia and the occurrence of hyperplastic and fundic gland polyps due to hypergastrinemia. [4][5][6] Furthermore, some studies have suggested that long-term PPI use might affect the progression of atrophic gastritis and the development of gastric cancer. 7,8 To overcome these limitations, gastric mucoprotective agents are frequently used alone or in combination with acid-suppressing agents.…”
Section: Introductionmentioning
confidence: 99%
“…Only 7 weeks after having withdrawn PPIs, an impressive picture of previously numerous fundic glands had changed significantly. Although there has been some debate on the impact of PPI on fundal gland polyp development [9], recent meta-analyses have concluded an association between long-term (> 12 months) use of PPI and fundic gland polyps [10,11]; our case adds a convincing example to this association.…”
Section: Discussionmentioning
confidence: 53%